2015
DOI: 10.3390/w7051889
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Quantification of Non-Point Source Pollution in a Meso-Scale Catchment for an Assessment of Buffer Zones Efficiency

Abstract: The objective of this paper was to spatially quantify diffuse pollution sources and estimate the potential efficiency of applying riparian buffer zones as a conservation practice for mitigating chemical pollutant losses. This study was conducted using a semi-distributed Soil and Water Assessment Tool (SWAT) model that underwent extensive calibration and validation in the Sulejów Reservoir catchment (SRC), which occupies 4900 km 2 in central Poland. The model was calibrated and validated against daily discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Among reasons for poor behavior in some stations, Marcinkowski et al [35] reported: (1) the dominant importance of global over local parameters in calibration; (2) simultaneous calibration of different pools of water quality parameters (with different optimal parameter sets achieved for different pools); and (3) input uncertainty (e.g., differences between defined agricultural management operations and the reality). A previous study applying SWAT in Poland for modeling water quality also showed that [41], frequently, the magnitude of the highest observed loads of nutrients is captured well by the model, but there is a shift in timing by a few days (the flood peak is sometimes advanced or lagged by 1-3 days compared with the timing of the peak identified in the observed data) which has a negative effect on the objective function value.…”
mentioning
confidence: 85%
“…Among reasons for poor behavior in some stations, Marcinkowski et al [35] reported: (1) the dominant importance of global over local parameters in calibration; (2) simultaneous calibration of different pools of water quality parameters (with different optimal parameter sets achieved for different pools); and (3) input uncertainty (e.g., differences between defined agricultural management operations and the reality). A previous study applying SWAT in Poland for modeling water quality also showed that [41], frequently, the magnitude of the highest observed loads of nutrients is captured well by the model, but there is a shift in timing by a few days (the flood peak is sometimes advanced or lagged by 1-3 days compared with the timing of the peak identified in the observed data) which has a negative effect on the objective function value.…”
mentioning
confidence: 85%
“…Therefore, bream can more successfully coexist with piscivores and increase their foraging efficiency with increasing reservoir trophy, thus benefiting from lower competition for food resources (Lammens 1989). According to the latest findings, external nutrient loading is decreasing due to different conservation practices aimed at mitigating diffuse pollution sources (e.g., establishing riparian buffer zones in agriculture (23) areas) upstream of the reservoir (Piniewski et al 2015). Considering these factors, the reason for the recently reversed trend in bream/roach biomass is unknown, but one potential explanation could be the decrease in the zebra mussel population, a recent phenomenon in Polish lakes due to environmental changes (Stańczykowska et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The minimum and maximum values presented in these tables are related to extreme values of parameters across the calibrated gauges and water quality monitoring points for each variable. Selection of the parameters set was made based on previous applications of the SWAT model under Polish conditions [PINIEWSKI et al 2014;PINIEWSKI et al 2015;MAR-CINKOWSKI et al 2013] and on the sensitivity analysis performed in both catchments. An important thing in the context of multi-site calibration is the fact that parameters are either global (i.e.…”
Section: Multi-site Calibrationmentioning
confidence: 99%
“…One of the most popular models is Soil and Water Assessment Tool (SWAT) which was applied in Europe across a range of spatial scales: from the whole continent , to largest river basins [ČERKASOVA et al 2016;PAGLIERO et al 2014;PI-NIEWSKI et al 2016], meso-scale catchments [OSTOJ-SKI et al 2014;PINIEWSKI et al 2015] and small catchments [BRZOZOWSKI et al 2011;MARCINKOW-SKI et al 2013;MOLINA-NAVARRO et al 2014; SMA-RZYŃSKA, MIATKOWSKI 2016;ŚMIETANKA 2014]. An increasing interest in the model triggers more com-plex and challenging applications, especially concerning implementation of new remote sensing techniques and datasets [AL-DOUSARI et al 2010] or more detailed multi-site and multi-variable calibration approach [WOZNICKI et al 2016].…”
Section: Introductionmentioning
confidence: 99%